Fabrication optimization and application of 3D hybrid SERS substrates. Issue 50 (22nd September 2021) - Geng, Xiaoyuan; Wu, Chen; Liu, Siying; Han, Yu; Song, Liang; Zhang, Yun
Abstract : The SERS effect of 3D hybrid substrate composed of AuNS and AuNO can be adjusted by changing the size and location of nanoparticles in the substrate, and SERS effect of the optimized substrate was better than that prepared by single nanoparticles. Abstract : Three-dimensional (3D) plasmonic nanostructures with nanoparticles that can be tuned have got a lot of attention in surface-enhanced Raman scattering (SERS) due to the unique 3D plasmonic coupling. Here, two nanoparticles, gold nanosphere (AuNS) and gold nanooctahedra (AuNO), were used to construct 3D hybrid SERS substrates to investigate the effect of nanoparticle spatial position on the SERS performance of the 3D nanostructure and to obtain 3D substrates with high SERS activity. And more hybrid combination possibilities were tested to explore the variation trend of hot spots generated when the nanoparticles were near. First, two-dimensional (2D) planar substrates were prepared using the air–liquid interface-assisted self-assembly method, to examine the effect of nanoparticle size on SERS performance. Then, 3D hybrid SERS substrates were further prepared layer by layer to discuss the effect of different combination methods within three layers on SERS performance. The optimized 3D hybrid substrate with the sandwich structure of AuNS/AuNO/AuNS performed the strongest SERS enhancement effect, whose intensity was 4.1 and 1.9 times that of AuNS/AuNS/AuNS and AuNO/AuNO/AuNO, respectively, and had good reproducibility (relative standard deviation (RSD) of 1.08%). Furthermore, the thiram molecular result showed that the prepared AuNS/AuNO/AuNS had good linear relationship ( R 2 of 0.991) and good molecule detection sensitivity (the minimum detection volume of thiram is 100 ppb), which demonstrated the great potential of the 3D hybrid SERS substrates in practical analysis.